La centauresse, un exemple de remise en question de la frontière du genre à l’époque impériale - Eléonore Montbel (Frontière·s)
The existence of sexual types (male, female) in a species creates a biological boundary common to any living species undergoing sexual reproduction. However, when it comes to mythical beings, this system has no necessity: in archaic and classic Greek imagination there are only male or female groups, such as sirens, satyrs or centaurs. However, the frontier of the genre is one day crossed and feminine counterpart are born, sometimes even accompanied by little centaurs, allowing a generation. These feminine variations of centaurs are attested in the figuration from the 1stc. BC, especially in domestic and funerary contexts. They thus appear as a "supplement" to their male counterparts : they appear later, are represented in much smaller numbers and are almost absent in literature – unlike them. This article aims to understand, from ancient figurative and written documentation, why centauresses are absent in the Greek world and why it was felt necessary in the 1stc. BC to go beyond the established imaginary and create a counterpart of the other sex.